2018
DOI: 10.1075/tis.00019.int
|View full text |Cite
|
Sign up to set email alerts
|

Community interpreting, translation, and technology

Abstract: The focus of ETHI-CA2 spans ethical aspects around the entire processing pipeline from speech and language, as well as multimodal resource collection and annotation, to system development and application. In the recent time of ever-more collection "in the wild" of individual and personal multimodal and multi-sensorial "Big Data", crowd-sourced annotation by large groups of individuals with often unknown reliability and high subjectivity, and "deep" and autonomous learning with limited transparency of what is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…The chapter called "Mapping the Field" (Napier, Skinner and Braun 2018: 11-35) reflects extensively on cognitive pressure, and strategies in interpreting via video link, both for spoken and signed language. Of course, the need for more research (not only replication research to substantiate findings but also more interdisciplinary research) can be linked to the already mentioned backlog in professionalisation, as confirmed once again by Mellinger and Pokorn (2018) in their introduction to the special issue of Translation and Interpreting Studies when referring to the then innovative The Routledge Encyclopedia of Translation Technology (Chan 2015): "Compared to the extensive body of research in the field of translation, research on the intersection of community interpreting and technology is still in its initial stages" (Mellinger and Pokorn 2018: 337). Let this be a call to all interpreting scholars to not simply stress the need of research in this area, but to do it!…”
Section: Dialogue Interpretingmentioning
confidence: 73%
“…The chapter called "Mapping the Field" (Napier, Skinner and Braun 2018: 11-35) reflects extensively on cognitive pressure, and strategies in interpreting via video link, both for spoken and signed language. Of course, the need for more research (not only replication research to substantiate findings but also more interdisciplinary research) can be linked to the already mentioned backlog in professionalisation, as confirmed once again by Mellinger and Pokorn (2018) in their introduction to the special issue of Translation and Interpreting Studies when referring to the then innovative The Routledge Encyclopedia of Translation Technology (Chan 2015): "Compared to the extensive body of research in the field of translation, research on the intersection of community interpreting and technology is still in its initial stages" (Mellinger and Pokorn 2018: 337). Let this be a call to all interpreting scholars to not simply stress the need of research in this area, but to do it!…”
Section: Dialogue Interpretingmentioning
confidence: 73%
“…Furthermore, the existing scholarly discussion on this subject primarily emphasizes CAI tools prior to interpreting and tools for consecutive interpreting. This work aims to portrait CAI tools in interpreter education in China, echoing the western researchers' appeal (e.g., Irabien, 2010;Fantinuoli, 2018;Mellinger & Pokorn, 2018) to replicate the previous studies in different regions with different language combinations, thus complementing the bigger picture of CAI tools used in educational settings in the world. measure in any way the use of CAI tools in the profession or in pedagogy, but rather to provide statistical information for both fields and may eventually better align teaching objectives with the demand for future interpreters.…”
Section: Literature Reviewmentioning
confidence: 90%
“…Over the last decade, increased attention has been paid to new technologies with new capabilities that have been developed in China, albeit accompanied by rash commercial fanfare 1 , which is seldom attempted in the western world. Following on the appeal of previous literature (e.g., Fantinuoli, 2018;Mellinger & Pokorn, 2018) to replicate or further the investigation of CAI tools in practice and interpreter education, this report, out of a series of related studies, presents an analysis of the perceptions of CAI tools in interpreter education from an online survey of student interpreters, professional interpreters, and interpreter trainers. It is hoped that the findings of this study will serve to profile the demand for CAI tools in China's interpreter education and help speed up integrating CAI in interpreter education.…”
Section: Introductionmentioning
confidence: 99%